SUMBER PENCEMAR DAS CILIWUNG SEGMEN 2 SERTA UPAYA PENANGGULANGANNYA - Astuti, Ariani Dwi; Iswanto, Bambang; Somantri, Berdi (Jurnal Teknologi Lingkungan Universitas Trisakti, 2008)
Pollutant Resources in Ciliwung Watershed Segment 2 and its Solutions. Ciliwung River flows across provinces West Java and DKI Jakarta and has a very important role to the people who lives along side it. According to Ministry of Environment in 2006, Ciliwung River’s drainage basin is divided to 5 segments. This Ciliwung River’s drainage basin segment 2 is in the Bogor municipalities and involving 16 villages. This research is to identify the resources and the variety of the pollution itself, and make the mapping for the vile level of the drainage basin area that has a correlation to the water’s quality, as a result of the activities from the people who lives in the segment 2 and recommends the effort to overcome it. The sample taken in 12 chosen points based on the allotment from the length of the river and the easily reached. The laboratory analysis result the highest BOD level founded in in Kedung Badak Pedes (12nd point) with concentration reaches 34,7 mg/l, COD in Kebon Pedes (11th point) reaches 39,95 mg/l, N in Paledang (7th point) reaches 11,25 mg/l and Fosfat in Babakan Pasar (6th point) reaches 0,267 mg/l . The vile level, as a result the vilest area is in Babakan Pasar based on the highest number of diarchea, Kedung Halang for the clean water supply, and Babakan Pasar and Sempur for the environmental sanitation. The source of the pollution in the segment 2 is organic material from domestic waste dropped to the river. Therefore, it is recommended to repair and to improve sanitation and clear water supply.   Abstract in Bahasa Indonesia:  Sungai Ciliwung melintasi provinsi Jawa Barat serta DKI Jakarta dan memiliki fungsi penting bagi masyarakat sekitar DAS. Menurut Kementrian Lingkungan Hidup tahun 2006, DAS Ciliwung ini terbagi atas 5 segmen. Segmen 2 ini berada pada wilayah kotamadya Bogor, meliputi 16 kelurahan. Penelitian ini bertujuan untuk mengidentifikasi sumber dan jenis pencemar, membuat pemetaan tingkat kekumuhan di DAS berkaitan dengan sanitasi dan pengaruhnya terhadap kualitas sungai, yang diakibatkan kegiatan penduduk di DAS Ciliwung segmen 2 serta menentukan upaya penanganannya. Pengambilan sampel dilakukan di 12 titik dan menunjukkan bahwa konsentrasi BOD tertinggi yaitu di Kedung Badak (di titik 12) dengan konsentrasi 34,7 mg/l, konsentrasi COD pada Kebon Pedes (di titik 11) dengan konsentrasi 39,95 mg/l, N pada Paledang (di titik 7) dengan konsentrasi 11,25 mg/l, dan Fosfat pada Babakan Pasar (di titik 6) dengan konsentrasi 0,267 mg/l. Untuk tingkat kekumuhan, angka kesakitan diare di Babakan Pasar tergolong Sangat Kumuh, Kedung Halang untuk tingkat pelayanan air bersih, serta Babakan Pasar dan Sempur untuk kondisi sanitasi lingkungannya. Sumber pencemar utama sungai Ciliwung segmen 2 adalah bahan organik dari limbah domestik (cair dan padat). Untuk itu salah satu program yang direkomendasikan adalah program peningkatan sarana sanitasi dan pelayanan air bersih.